Perspektif Ekonomi Syariah Di Indonesia Tentang Riba, Bunga Bank, dan Bagi Hasil - Hisam Ahyani (Universitas Siliwangi, 2021)
Introduction / Main Objective : This study aims to reveal the existence of community conceptions related to profit sharing (Sharia economics), usury, bank interest (conventional), in terms of Islamic economics, where these 3 (three) things are unique and interesting if we discuss in the era of disruption like today. Background: The era of discipline 4.0 as it is now is very interesting and unique regarding the study of the prohibition of usury in Indonesia, what is unique is the Khilafiyah which is the basis for especially Muslims (sharia economic actors), the need for tolerance between the views of schools of thought in Indonesia regarding this usury in sharia economics (muamalah) in order to benefit together in this world and in the hereafter. Research Methods: This study uses the Library Research Method and collects data obtained by means of literature studies from books and journals relevant to studies on usury and bank interest (conventional), profit sharing (Islamic economics).Novelty: Related to research on the perspective of Islamic economics in the current era of disruption, especially in Indonesia regarding usury, and bank interest (conventional), as well as profit sharing (Islamic economics) so far no one has examined it.Findings: from a sharia economic point of view related to profit sharing, usury and also bank interest have a good impact on the economy in Indonesia, where the profit sharing system can help people in terms of social resilience, and overcome social inequalities (making tahsin / benefit of the ummah).Conclusion: The public, in their view of usury, bank interest and profit sharing within the Islamic economic community, requires tolerance in punishing these three things, as a result there is no